Changes in the Composition of Foundation's Organs Without Supervisory Board Meetings and the Foundation's Articles of Association - merry kalyana; Antarin Prasanthi Sigit (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Changes to the composition of the foundation's organs should be based on a meeting of the supervisors or determined otherwise based on the foundation's articles of association. This is to provide certainty for foundations to carry out legal actions, both internally and externally. However, in practice there are also changes in the composition of organs that are not in accordance with the regulations in Article 28 in conjunction with Article 32 in conjunction with Article 44 of Law Number 28 of 2024, an amendment to Law Number 16 of 2001 concerning Foundations, hereinafter referred to as the Foundation Law. This of course can trigger development due to legal flaws as found in the case of the Banjarmasin High Court Decision Number 83/PDT/2022/PT BJM, the dispute in the a quo decision was triggered by changes to the foundation's organs which resulted in a meeting which may not have decided. cessation of foundation organs. Therefore, the aim of this research is to analyze the results of legal changes to foundation organs that are not based on supervisory meetings or based on the provisions of the foundation's articles of association. As well as, analyzing legal protection for administrators who are dismissed from their positions based on meetings that do not have the right to make dismissal decisions. This doctrinal legal research collects secondary data through literature study, which is then analyzed qualitatively. From the results of the analysis, it can be explained that the legal consequences of changes to the foundation's organs that do not comply with the provisions as found in the case of the a quo decision are that the legal consequences of changes to the composition of the foundation's organs that are not based on a meeting of supervisors or provisions in the Articles of Association are invalid and null and void by law. because changes to the composition of the foundation's organs are part of changes to the articles of association regulated in article 18 of the Foundation Law. As for legal protection for administrators who are dismissed from their positions based on meetings where decisions are not appropriate, preventive legal protection is carried out in the realm of administrative, civil and criminal law which gives rise to The obligation to pay compensation by the Defendant to the Plaintiff as the injured party and dispute resolution arise from the existence of repressive legal protection through the courts.